Henri Bergson et les conservateurs espagnols (1907-1940)/II - Camille Lacau Saint-Guily (Cahiers de Civilisation Espagnole Contemporaine, 2013)
Faced with the intransigence of the Catholic néothomiste orthodoxy, is a Catholic modernist Bergsonism possible in Spain? The friendship of the two French, Jacques Chevalier and Maurice Legendre -great disciples of Bergson and whose liberal catholicism is inspired by Bergsonism- with Miguel de Unamuno and Juan Domínguez Berrueta, contributed to the emergence of a Spanish Bergsonian mysticism in the 1910s. Berrueta uses Bergsonism to adapt the post-Tridentine mystic of Sta Teresa and San Juan de la Cruz. Bergson helps to restore, in those times of Catholic intellectualism, the mystical side of Christianity and Catholicism. Berrueta also relies on him to reconnect with the Augustinian and Franciscan tradition of immanent contemplation in the quest for God. Juan Zaragüeta also reveals the presence of a Catholic Bergsonism in the peninsula, conciliating the unthinkable in this country more than elsewhere, i.e. neo-Thomism and Bergson.